ANATOMICAL LOCATION AND RELATIONSHIP OF MENTAL FORAMEN IN MANDIBULAR FRACTURES - Muhammad Dilshad; Shahid Ali; Iqra Amin (Pakistan Oral & Dental Journal, 2021)
The widespread morbidity and mortality associated with maxillofacial trauma have made it an interesting topic for researchers for several years. The mental foramen is situated on the anterolateral aspect of the body of mandible. There is scarce study for the position of mental foramen and its relation to mandibular fracture site in Pakistani population. The aim of this study was to determine the frequency of various anatomical positions of mental foramen, in patients with mandibular fracture and to detect relationship (fracture line passing through mental foramen or not) of mandibular fracture line with mental foramen. This Cross sectional study was conducted at the Department of Oral & Maxillofacial Surgery, Punjab Dental Hospital, Lahore for 6 months. After meeting the inclusion criteria 107 patients were enrolled. Mental foramen position was noted as Position 1 if it was in line with the long axis of 1st premolar, as Position 2 if it was between 1st & 2nd premolar, as Position 3 if it was in line with the 2nd premolar and Position 4 if it was anterior to 1st premolar or distal to second premolar. Mandibular fracture line was noted in relation to mental foramen; either fracture line is passing through the mental foramen or not. In this study the average age of patients was 36.64Â±13.60 years. Parasymphyseal site of fracture noted in 49(45.8%) patients. The mental nerve foramen position between 1st and 2nd premolar was noted in 75(70.09%) patients, while the fracture line passing through the mental nerve foramen was observed in 13(12.15%) patients. According to the present study the most common anatomical positions of mental foramen was between 1st & 2nd Premolar and approximately 10% of the patients appeared with line passing through the mental foramen.